ANALISA EFEKTIVITAS ANGGARAN BELANJA DINAS PEKERJAAN UMUM BINA MARGA PROVINSI JAWA TIMUR - Thianka Salsabila Ayu Prasyah; Binti Shofiatul Jannah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to evaluate the level of effectiveness of the direct expenditure budget of the East Java Province Bina Marga Public Works Office in 2021-2023. The results of the analysis show that the level of effectiveness reached 100%, reflecting the use of a very effective budget and optimal performance in financial management. However, an evaluation of budget efficiency cannot be carried out due to the absence of indirect expenditure budget data in the Annual Performance Report (LKj). This highlights the importance of improving transparency and accuracy in budget reporting to support more thorough performance evaluation in the future